Imperatyw, ironia i przemyt wierzbowych gruszek. Notatki o wierszu Do Jeruszalaim Jerzego Ficowskiego - Czwordon, Paulina (Poznańskie Studia Polonistyczne. Seria Literacka, 2009)
The poem Do Jeruszalaim combines different original poetical solutions applied in the collection of poems Odczytanie popiołów and remembering the experience of Shoah. The language of the poem becomes a tool employed in a “smuggling” of unsaved Jews, being done “belatedly”, into the world of the living. Complicated, unspectacular by design, constructional operations are finely tuned with the semantics of the escape (flight) and are to lay a false trail, to rescue a human being in the intricacies of the poem, somewhere between the sheer physics of the escape and the possibilities offered by words. A particularly interesting place is given to the phraseological units used in the poems such as “a handful of pies in the sky” that simultaneously recall futility of the action but somehow suggest a “smuggling” the act of life-giving activity. The activities carried out in the language of the poem function in a ceaseless (and self-augmenting) strain between the two contradictions. They are: the imperative of memory, impractical (and unfeasible) act of saving human “after-being” and the protest against the abyssmal nothingness of Shoah on the one hand, and irony of the futility of these “vindications from non-existence” as being only verbal, on the other.